Broadband transient full-Stokes luminescence spectroscopy - Antti-Pekka M. Reponen; Marcel Mattes; Zachary A. VanOrman; Lilian Estaque; Grégory Pieters; Sascha Feldmann (Nature, 2025)
Abstract Materials emitting circularly polarized light (CPL) are highly sought after for applications ranging from efficient displays to quantum information technologies1–7. However, established methods for time-resolved CPL (TRCPL) characterization have notable limitations8–17, generally requiring a compromise between sensitivity, accessible timescales and spectral information. This has limited the acquisition of in-depth photophysical insight necessary for materials development. Here we demonstrate a high-sensitivity (noise level of the order of 10−4), broadband (about 400–900 nm), transient (nanosecond resolution, millisecond range) full-Stokes (CPL and linear polarizations) spectroscopy setup. The achieved combination of high-sensitivity, broad wavelength response and flexible time ranges represents a substantial advancement over previous TRCPL approaches. As a result, TRCPL measurements are shown to be applicable to hitherto inaccessible material systems and photophysical processes, including systems with low (10−3) dissymmetry factors and luminescence pathways spanning nanosecond to millisecond time ranges. Finally, full-Stokes measurements allow tracking the temporal evolution of linear polarization components, of interest by themselves, but especially relevant in the context of controlling for associated CPL artefacts18,19 in the time domain.